Automation of Java Code Analysis for Programming Exercises - Köllmann, Carsten; Goedicke, Michael (Electronic Communications of the EASST, 2007)
In this paper we present a tool environment for semi-automatic verification of basic programming exercises. We describe how graph transformation can be used for analysis of code structures and present an example from a current course.